ChemInform Abstract: A Novel and Efficient Route to Azabicycles via the Isocyanate‐Mediated Twofold Cyclization. Issue 27 (16th June 2016) - Li, Mingming; Xing, Ping; Jiang, Biao
Abstract: Compounds with an azabicyclic skeleton can be prepared from easily available allylic alcohols of type (I).